Jim Averbeck presents A Hitch at the Fairmont - Averbeck, Jim (Atheneum Books for Young Readers, 2014)
When his aunt is kidnapped, an eleven-year-old boy staying at San Francisco's Fairmont Hotel in 1956 tries to find her, with the help of Alfred Hitchcock.